2014
DOI: 10.5455/jbh.20140106021749
|View full text |Cite
|
Sign up to set email alerts
|

Patient and treatment related variables as predictors of length of stay in a Nigerian Neuropsychiatric hospital.

Abstract: Aim: The aim of this study was to assess the hospital length of stay (LOS) of patients discharged from the acute wards of a psychiatric hospital in Nigeria and to determine its relationship with demographic, illnessrelated and treatment related variables. Methods: This was a retrospective cross-sectional study involving case note review of patients discharged from the acute psychiatric ward of the hospital during 1-year period. A questionnaire was used in collecting data about the socio-demographic variables (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This type of communication is most important for patients with low educational levels and limited functional health literacy because such patients are likely to make medication errors and act inappropriately in response to the side effects of the drugs. 34 Such quality communication helps to meet therapeutic goals, eventually promoting recovery from illness and achieving a better quality of life. In this regard, a meta-analytic review concluded that health professionals who adopt a warm and act friendly are more effective than those who keep consultations formal and do not offer reassurance to their clients.…”
Section: Resultsmentioning
confidence: 99%
“…This type of communication is most important for patients with low educational levels and limited functional health literacy because such patients are likely to make medication errors and act inappropriately in response to the side effects of the drugs. 34 Such quality communication helps to meet therapeutic goals, eventually promoting recovery from illness and achieving a better quality of life. In this regard, a meta-analytic review concluded that health professionals who adopt a warm and act friendly are more effective than those who keep consultations formal and do not offer reassurance to their clients.…”
Section: Resultsmentioning
confidence: 99%
“…bles of primary interest. In contrast, most previous studies focused on patient-related factors including sociodemographic and clinical factors [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], hospital or regional characteristics [6,[15][16][17]21], or provider-or service-related factors [18][19][20][21][22], less on legal factors. For example, some studies included legal status as a predictor of LOS but did not show the actual day information [6,21]; specifically, Compton et al reviewed legal status at admission and at discharge, not court-ordered treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Balancing Legal and Clinical Concerns also been associated with LOS [6][7][8][9][10][11][12][13][14]. Clinical factors such as a primary diagnosis of schizophrenia and a greater number of previous admissions predicted longer LOS [5][6][7][8][9][10].…”
Section: Original Articlementioning
confidence: 98%